Chemistry private tutoring in Malaysia - Low Suan Ee; Nor Hasniza Ibrahim; Johari Surif (International Journal of Evaluation and Research in Education (IJERE), 2023)
The unsatisfactory result obtained by Malaysian secondary students in international assessment has caused the Ministry of Education to put much effort into structuring the curriculum. Variety of teaching pedagogies has been suggested but not all the approaches are applicable due to many constraints. It leads students to enroll in extra private tutoring classes after their regular school hours. This research aimed to identify the reason students attend chemistry private tutoring, to explore the teaching pedagogies used in chemistry private tutoring, and to identify the perceptions of students on the pedagogies used in chemistry private tutoring. This is an exploratory qualitative study that is conducted among six tutors and five students in Malaysia. The result was analyzed through thematic analysis. Interestingly, the study has indicated that despite improving their academic result, students attend tuition to enhance their understanding and knowledge of chemistry as they were ably exposed to a variety of teaching methods. A new insight on pedagogies used in private tutoring lessons was determined, such as deductive learning, inquiry-based teaching and contextualization. It is found that student’s learning needs are highly emphasized in tuition classes. Students experience more meaningful learning and obtain interesting learning experiences in tuition.